Intracranial subdural haematoma following neuraxial anaesthesia in the obstetric population: a literature review with analysis of 56 reported cases. (February 2016) - Cuypers, V.; Van de Velde, M.; Devroe, S.
Highlights: Intracranial subdural haematoma is a rare but serious complication of neuraxial anaesthesia. Consequences can be significant especially in young and healthy obstetric patients. A flow chart on how to assess postpartum headache after neuraxial procedures is made. Vigilance is required whenever a headache becomes prolonged and non-postural. Abstract: Background: Intracranial subdural haematoma is a rare but serious complication of neuraxial anaesthesia. With early diagnosis and treatment, severe neurological sequelae can be avoided. A literature search of intracranial subdural haematoma following neuraxial anaesthesia in obstetric patients was performed. Based on the findings, a flow chart on how to assess postpartum headache following a neuraxial procedure is proposed. Methods: Medline, Embase and Cochrane databases were searched for cases of intracranial subdural haematoma following neuraxial anaesthesia in obstetric patients. Epidemiological factors, clinical symptoms and signs, treatment, outcome and the effect of performing an epidural blood patch were assessed. Results: Review of the literature identified 56 cases following neuraxial procedures (epidural n=34, spinal n=20, combined spinal-epidural n=2). Predisposing risk factors were present in only a minority of patients. Persistent headache that stopped responding to postural change was the most important symptom with occurrence in 83% of patients. Focal neurological signs were present in 69% of women. Eleven percent of women were left with residual neurological deficits; the mortality rate was 7%. Conclusion: Intracranial subdural haematoma following neuraxial anaesthesia in obstetric patients is rare but serious complications may result. Vigilance is required whenever a headache becomes non-postural, prolonged and/or whenever focal neurological signs occur.